2018
DOI: 10.4081/mr.2017.5564
|View full text |Cite
|
Sign up to set email alerts
|

Enteric fever cases showing concurrent seropositivity with Dengue and malaria: A sero-diagnostic challenge

Abstract: Enteric fever, Dengue and malaria still remain diseases of public health importance in the tropics. Individuals residing in endemic areas are at risk of contracting these infections either concurrently or an acute infection superimposed on a chronic one. This study was undertaken to document patients showing co seropositivity for Enteric fever, Malaria and Dengue and to record the baseline Salmonella antibody titer in voluntary blood donors who represent general population of the area. The present study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The result of our study on 80 patients which included dengue and COVID-19 positive patients and 30 healthy control subjects showed around two in four subjects serum samples antibody titre of Salmonella enteric serovar typhi O and H antigen were more than 1:20 and 1:40, which is similar to the study done by Ramya and Sunitha where they found 42% of their study population had anti O titers above 1:20 and 52% had anti H titres above 1:20 against serotype S.typhi. 1 In the present study, among the dengue IgM positive patients 20% samples antibody titre of O Ag of Salmonella enteric serovar typhi were 1:80 and antibody titre for H antigen were 1:160, and they also showed IgM positive bands on ICT test. However, their blood culture showed no growth after 5 days of incubation and clinically no signs and symptoms of typhoid fever.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The result of our study on 80 patients which included dengue and COVID-19 positive patients and 30 healthy control subjects showed around two in four subjects serum samples antibody titre of Salmonella enteric serovar typhi O and H antigen were more than 1:20 and 1:40, which is similar to the study done by Ramya and Sunitha where they found 42% of their study population had anti O titers above 1:20 and 52% had anti H titres above 1:20 against serotype S.typhi. 1 In the present study, among the dengue IgM positive patients 20% samples antibody titre of O Ag of Salmonella enteric serovar typhi were 1:80 and antibody titre for H antigen were 1:160, and they also showed IgM positive bands on ICT test. However, their blood culture showed no growth after 5 days of incubation and clinically no signs and symptoms of typhoid fever.…”
Section: Discussionsupporting
confidence: 48%
“…Typhoid and Dengue fever are the most concurrent diseases in the tropical country for many years and along with these, coronavirus emerged as one of the most lethal disease in the world. 1 Although these diseases are caused by two separate agents, they have some similar symptoms which can easily end up with misdiagnosis. So, diagnosis of the causative agents is important in the treatment of these diseases which are directly related with population density, urbanization, endemicity, mobility as well as mortality.…”
Section: Introductionmentioning
confidence: 99%